Box dynamics: A sectoral approach to analyse containerized port throughput interdependencies. (December 2017) - Paflioti, Persa; Vitsounis, Thomas K.; Teye, Collins; Bell, Michael G.H.; Tsamourgelis, Ioannis
Abstract: Port throughput is the aggregation of products handled in a port and depends on the performance of relevant interdependent industries. In depth understanding of the fluctuations of a port's activities at the aggregate level requires a granular analysis at the disaggregate level. This becomes more critical in the case of containers since in general limited information for a container's content is available. In the present study Sydney's container port throughput is decomposed in its main industrial sectors and focus on their interrelations. Quarterly data are used covering the 2014:Q3 – 1995:Q2 period and 15 sectors in line with United Nations classification. For the identification of spillover shocks across container sectors over time we develop a "spillover index" on the basis of a Vector Autoregressive (VAR) model. The interpretation of the results is enhanced with the use of network theory. The results document that fluctuations on the aggregate level are the output of co-movement across container sectors for both imports and exports, while at the same time they respond differently to shocks revealing "leadership" and "followship" behavior. Finally, the main macroeconomic determinants affecting the co-movement of sectors demonstrate different sign and significance for exports and imports.